Perishing rich, expanding poor: Demography and population genetic patterns in two congeneric butterflies. Issue 3 (30th November 2022) - Konvickova, Hana; Spitzer, Lukáš; Fric, Zdenek Faltynek; Kepka, Pavel; Lestina, Dan; Novotny, David; Zapletal, Michal; Zimmermann, Kamil; Maresova, Jana Papp; Benes, Jiri; Konvicka, Martin
Abstract: In human‐altered landscapes, specialist butterflies typically form spatially restricted populations, genetically differentiated due to dispersal restrictions. Generalists, in contrast, display minimum differentiation but high genetic diversity. While local‐level actions suffice to conserve specialists and landscape‐level actions are necessary for generalists, minimum information exists regarding conservation of species with intermediate features. We targeted two congeneric butterflies, the recently re‐expanding Argynnis adippe and the strongly declining A. niobe, co‐occurring in the pastoral landscape of the Carpathian Mountains, Czech Republic. We integrated species distribution models, mark–recapture and microsatellite analysis to compare their habitat requirements, adult demography, dispersal and genetic patterns, and expanded the genetic analysis across the Carpathian Arc and beyond to delimit spatial conservation units. In two mountain valleys, both species formed interconnected populations numbering thousands of individuals. Mobility patterns suggested the populations' interconnection across the Czech Carpathians. Genetic diversity was extremely poor in the nonthreatened A. adippe and moderate in the declining A. niobe . No population differentiation was detected within the Czech Carpathians ( 1500 km 2 ). Low genetic diversity and no differentiation was preserved in A. adippe across East Central Europe, whereas in A. niobe, populations from Serbia were differentiated from the Carpathian Arc + Alps. The high adult mobility linked to low differentiation probably reflects the distribution of larval resources, historically widespread but sparse and currently declining for A. niobe (grazing‐disturbed grounds), while currently increasing for A. adippe (abandonment scrub, disturbed woodlands). Units as large as entire mountain systems define population boundaries, and hence conservation management units, for both species.